DEVELOPMENT OF NUMERACY LITERACY INSTRUMENTS IN ALGEBRA MATERIAL CLASS X VOCATIONAL SCHOOL - Bastian, Heri; Nindiasari, Hepsi; Sukirwan, Sukirwan (Tesseract: International Journal of Geometry and Applied Mathematics, 2024)
This research aims to produce a Mathematics numeracy literacy instrument on algebra liner material in vocational schools that is tested for validity and reliability, as well as through systematic analysis of instruments with differentiating power tests and difficulty indexes. This type of research is a development study with the Wilson model and the Oriondo and Antonio model. The data collection method uses interviews, expert validation sheets, questionnaires and numeracy literacy tests. The data were analyzed descriptively and quantitatively. The results of the research obtained are: 1) expert assessment states that this numeracy literacy instrument is an instrument that is suitable for use; 2) the readability test shows that this numeracy literacy instrument is categorized as "good", 3) the validity test shows that this instrument is valid; 4) this numeracy literacy instrument is a reliable instrument with a reliability value of ri>rtable; 5) it has a good interpretive power with the conclusion that it can be used without revision; 6) Medium average difficulty index of question items. So that the resulting instrument is an instrument that is suitable for measuring students' numeracy literacy. This research aims to produce a Mathematics numeracy literacy instrument on algebra liner material in vocational schools that is tested for validity and reliability, as well as through systematic analysis of instruments with differentiating power tests and difficulty indexes. This type of research is a development study with the Wilson model and the Oriondo and Antonio model. The data collection method uses interviews, expert validation sheets, questionnaires and numeracy literacy tests. The data were analyzed descriptively and quantitatively. The results of the research obtained are: 1) expert assessment states that this numeracy literacy instrument is an instrument that is suitable for use; 2) the readability test shows that this numeracy literacy instrument is categorized as "good", 3) the validity test shows that this instrument is valid; 4) this numeracy literacy instrument is a reliable instrument with a reliability value of ri>rtable; 5) it has a good interpretive power with the conclusion that it can be used without revision; 6) Medium average difficulty index of question items. So that the resulting instrument is an instrument that is suitable for measuring students' numeracy literacy.